2020
DOI: 10.1101/2020.05.29.20116111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted sequencing of Parkinson’s disease loci genes highlightsSYT11, FGF20and other associations

Abstract: Genome-wide association studies (GWAS) have identified numerous loci associated with Parkinson's disease. The specific genes and variants that drive the associations within the vast majority of these loci are unknown. We aimed to perform a comprehensive analysis of selected genes to determine the potential role of rare and common genetic variants within these loci. We fully sequenced 32 genes from 25 loci previously associated with Parkinson's disease in 2,657 patients and 3,647 controls from three cohorts. Ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Parkinson's disease (PD) is a neurodegenerative disorder that predominately affects dopaminergic neurons in the substantia nigra of the brain (Y. Liu, Deng, et al, 2021). Genetic association analysis indicates that polymorphisms in FGF20 may be significantly associated with an increased risk of PD in Chinese and Indian populations (Jing et al, 2015; Rudakou et al, 2021; Sadhukhan et al, 2018; X. Y. Sun, Wang, et al, 2017; X. Wang, Sun, et al, 2017; X. Zhao, Wu, et al, 2016).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…Parkinson's disease (PD) is a neurodegenerative disorder that predominately affects dopaminergic neurons in the substantia nigra of the brain (Y. Liu, Deng, et al, 2021). Genetic association analysis indicates that polymorphisms in FGF20 may be significantly associated with an increased risk of PD in Chinese and Indian populations (Jing et al, 2015; Rudakou et al, 2021; Sadhukhan et al, 2018; X. Y. Sun, Wang, et al, 2017; X. Wang, Sun, et al, 2017; X. Zhao, Wu, et al, 2016).…”
Section: Fgf Signaling In the Brain And Sensory Organsmentioning
confidence: 99%
“…39 And finally, it is hoped that in the future, the availability of a larger dataset would enable us to integrate additional layers of genetic data, including rare and copy number variants. 40 Our findings clearly highlight the importance of combining GWAS from diverse populations, representative of worldwide populations, to refine the genetic architecture underlying a complex trait such as AAO. Our COURAGE-PD dataset suggests a role for additional pathways in addition to α-synuclein mechanisms of modulating PD pathogenesis and influencing AAO in worldwide PD populations.…”
Section: Discussionmentioning
confidence: 69%
“…uncertainty associated with random X Chr inactivation, we excluded the X Chr variants from the present analysis 39 . And lastly, it is hoped that in the future, the availability of a larger dataset would enable us to integrate additional layers of genetic data, including rare and copynumber variants 40 .…”
Section: B)mentioning
confidence: 99%
“…It was reported that GPNMB was abnormal expressed in various cells [ 24 , 44 ]. Besides, genome-wide association studies demonstrated that GPNMB should be considered as possible Parkinson’s disease-related genes for future studies [ 45 ]. Thus, we further investigate the effect of GPNMB in MALAT1/miR-135b-5p regulated the proliferation and apoptosis of neurons in PD.…”
Section: Discussionmentioning
confidence: 99%